A Continuity of Voices in Russell Banks’s A Permanent Member of the Family - Anne-Laure Tissut (Sillages Critiques)
Why do certain works seem to address us compellingly? This paper attempts to provide elements for an answer by putting forward the notion of a “voice of the text.” Taking Russell Banks’s short story collection A Permanent Member of the Family as its example, it explores some of the modalities whereby readers may trace singular and changing paths through the text that are shaped by their own history and sensibility as much as by the text’s potentials. Through the study of the becoming of the text, whose status as an apparently frozen object is questioned, one hopes to approach the complexity of the mental representation referred to whenever the title of a literary work is mentioned.